Kemampuan memproduksi inulinase isolat khamir hasil isolasi dari Nira Siwalan (Borassus flabellifer L.) dengan variasi konsentrasi - Siti Maisaroh; Wijanarka Wijanarka; Agung Suprihadi (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2020)
Microbial inulinase is one of the most interesting enzymes, especially the ones produced by yeast. Yeast is commonly found in sugar-containing materials, such as Nira Siwalan (Borassus flabellifer L). Yeast uses simple sugar compounds in foods to obtain its energy. If the nira is stored, the fermentation begins to occur, carried by the natural microorganism of Nira Siwalan which causes sour taste as acetic acid is started to be formed. This condition is ideal for the microorganisms (such as yeast) to grow. This research aims to analyze the impact of the best calcium concentration towards the production of inulinase by indigenous yeast in Nira Siwalan (Borassus flabellifer L). The research was done in biotechnology laboratory, Biology Department, Faculty of Science and Mathematics, Diponegoro University. The activity of inulinase was determined using DNS method. The research was designed using Randomized Factorial Design with concentration of CaCl2 and incubation time as the factors. The CaCl2 concentration was differentiated into four categories: Ca0, Ca0.5, Ca1.0, and Ca1.5, while the incubation time was differentiated into 5 categories: T0, T4, T8, T12, T16, and T20. Each treatment is repeated three times. After that, the data obtained from the observation analyzed using ANOVA. The result shows that the addition of 0.5 mM CaCl2 with inulinase activity 0.555 IU/mL gives the best result.